Quality of seeds and senescence of soybean genotypes under two levels of bugs infestation (Pentatomidae) - Lustosa, Paulo Rogério; Zanuncio, José Cola; Leite, Germano Leão Demolin; Picanço, Marcelo (Pesquisa Agropecuaria Brasileira, 1999)
The objective of this research was to evaluate the genotypes CR-1 and CR-3, from the genetic improvement program of soybean flavor of the Federal University of Viçosa, in Viçosa, MG, Brazil, under two levels of Heteroptera infestation. The genotypes tested were CR-1, CR-3, Cristalina, Davis (susceptible genotype) and IAC-100 (resistant genotype). The genotypes CR-1, CR-3, Davis and Cristalina under low level of infestation (2.8 Heteroptera/beating) produced similar percentage of normal seeds (57%) but inferior to the genotype IAC-100 (77%). Under high level of infestation (6.42 Heteroptera/beating), the genotypes CR-1, CR-3 and Cristalina produced similar percentage of normal seeds but inferior to the genotypes Davis (43%) and IAC-100 (59%). All genotypes showed low level of leaves retention (less than 6%) when cultivated under low level of infestation by Heteroptera but under high level of infestation of these bugs, the genotypes CR-1 and IAC-100 showed smallest level of leaf retention (less than 5%) followed by Davis and CR-3 (6-20%) and Cristalina (21-40%). The genotypes CR-1, IAC-100 and Davis showed no green stem under low infestation, contrary to what was registered for CR-3 (3.6% green stem) and Cristalina (11% green stem). IAC-100, CR-1, and Davis showed the smallest percentages of plants with green stem (6.4, 10.3 and 18.3%, respectively) compared to CR-3 (64.8%) and Cristalina (77.3%).